Contradictions in judicial support for capital punishment in India and Bangladesh: utilitarian rationales - Hoyle, C; Lehrfreund, S (Springer, 2019)
India and Bangladesh share a common history, and each has developed somewhat similarly since partition. However, while both countries now have relatively low murder rates, India has seen a decline in the rate of executions, while Bangladesh continues to impose death sentences and carry out executions at a higher rate. There have been challenges to the death penalty in India, restricting its use to exceptional cases. The same has not occurred in Bangladesh. Yet in both countries, systemic flaws in the criminal process are evident. This article draws on two original empirical research projects that explored judges’ opinions on the retention and administration of capital punishment in India and Bangladesh. The data expose justice systems marred by corruption, incompetence, abuses of due process, and arbitrary and inconsistent treatment of defendants from arrest through to conviction and sentencing. It shows that those with the power to sentence to death have little faith in the integrity of the criminal process. Yet, a startling paradox emerges from these studies; despite personal knowledge of its flaws, judges have trust in the death penalty to deter crime and to realise other sentencing aims and feel retention benefits society. This is explained by reference to utilitarian values. Not only did our judges express strongly utilitarian justifications for sentencing people to death, in terms of their erroneous belief in its deterrent effect, but some also articulated utilitarian justifications for misconduct in pre-trial processes, suggesting that it was necessary to break the rules to secure convictions when the system was dysfunctional and ineffective.